PENGARUH LOVE OF MONEY, SIFAT MACHIAVELLIAN DAN TINGKAT PENGETAHUAN AKUNTANSI TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI: STUDI KASUS PADA MAHASISWA S1 AKUNTANSIUNIVERSITAS MUHAMMADIYAH METRO - Isa, Alma Choiril; endri, Nedi H; Sari, Gustin Padwa (Universitas Muhammadiyah Metro, 2022)
This research was conducted to determine the effect of love of money, machiavellian character and the level of accounting knowledge on the ethical perceptions of accounting students (a case study of accounting students at Muhammadiyah University of Metro). The research method in this research was quantitative. The sample used in this study were accounting students in the seventh semester (VII). By using purposive sampling technique in sampling, in order to obtain a sample of 68 respondents. The data were processed using the SPSS.20 output with multiple linear regression analysis. The result obtained was that the machiavellian nature influenced on the ethical perceptions of accounting students. Meanwhile, love of money and the level of accounting knowledge had no effect on the ethical perceptions of accounting students.